Tonsillectomy versus Tonsillotomy for Sleep-Disordered Breathing in Children: A Meta Analysis - Wang, Hui (PLoS One, 2015)
OBJECTIVES: Tonsillotomy has gained popular acceptance as an alternative to the traditional tonsillectomy in the management of sleep-disordered breathing in children. Many studies have evaluated the outcomes of the two techniques, but uncertainty remains with regard to the efficacy and complications of tonsillotomy versus a traditional tonsillectomy. This study was designed to investigate the efficacy and complications of tonsillotomy versus tonsillectomy, in terms of the short- and long-term results. METHODS: We collected data from electronic databases including MEDLINE, EMBASE, and the Cochrane Library. The following inclusion criteria were applied: English language, children, and prospective studies that directly compared tonsillotomy and tonsillectomy in the management of sleep disordered breathing. Subgroup analysis was then performed. RESULTS: In total, 10 eligible studies with 1029 participants were included. Tonsillotomy was shown to be advantageous over tonsillectomy in short-term measures, such as a lower hemorrhage rate, shorter operation time, and faster pain relief. In long-term follow-up, there was no significant difference in resolution of upper-airway obstructive symptoms, the quality of life, or postoperative immune function between the tonsillotomy and tonsillectomy groups. The risk ratio of SDB recurrence was 3.33 (95% confidence interval = 1.62 6.82, P = 0.001), favoring tonsillectomy at an average follow-up of 31 months. CONCLUSIONS: Tonsillotomy may be advantageous over tonsillectomy in the short term measures and there are no significant difference of resolving obstructive symptoms, quality of life and postoperative immune function. For the long run, the dominance of tonsillotomy may be less than tonsillectomy with regard to the rate of sleep-disordered breathing recurrence.